2010
DOI: 10.1002/mnfr.200900246
|View full text |Cite
|
Sign up to set email alerts
|

Significance of vitamin A to brain function, behavior and learning

Abstract: Retinoid acid, the bioactive metabolite of vitamin A, is a potent signaling molecule in the brains of growing and adult animals, regulates numerous gene products, and modulates neurogenesis, neuronal survival and synaptic plasticity. Vitamin A deficiency (VAD) is a global health problem, yet our knowledge of its effects on behavior and learning is still emerging. Here we review studies that have implicated retinoids in learning and memory deficits of post-embryonic and adult rodent and songbird models. Dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 47 publications
1
62
0
3
Order By: Relevance
“…Numerous behavioral studies in animal models have pointed to behavioral changes in rodents when the balance of RA is disrupted, either from exposure to excess or deficiency (Bremner et al, 2012;Olson and Mello, 2010). Finding in our study suggested that isotretinoin treatment in both healthy (Iso group) and hypothyroid animals H+Iso may affect brain monoamines system, providing a possible biological mechanism by which isotretinoin treatment could lead to depressive disorders.…”
Section: Discussionsupporting
confidence: 51%
“…Numerous behavioral studies in animal models have pointed to behavioral changes in rodents when the balance of RA is disrupted, either from exposure to excess or deficiency (Bremner et al, 2012;Olson and Mello, 2010). Finding in our study suggested that isotretinoin treatment in both healthy (Iso group) and hypothyroid animals H+Iso may affect brain monoamines system, providing a possible biological mechanism by which isotretinoin treatment could lead to depressive disorders.…”
Section: Discussionsupporting
confidence: 51%
“…38 Vitamin A (retinoic acid), it is a bioactive metabolite and a potent signalling molecule in the brains which modulates neurogenesis, neuronal survival, synaptic plasticity and regulates numerous gene products. 39 Vitamin E is the major component of the cell antioxidant defence system and has numerous important roles in the body due to its antioxidant activity. 40 The most abundant macroelements detected were Calcium (Ca), Potassium (K), Iron (Fe) and Sodium (Na).…”
Section: Discussionmentioning
confidence: 99%
“…Retinoik asit, özellikle erken embryogenezde önemli bir sinyal molekülüdür. [25] Vitamin A ve türevleri, retinoid reseptörleri aracılığı ile gen transkripsiyonunu düzenleyerek hücresel süreçlerde rol oynar. Bu reseptörler, retinoik asit reseptörleri (RAR) ve retinoid X reseptörleri (RXR) olmak üzere 2 gruba ayrılır.…”
Section: Gen Regülasyonu Ve Sinyal Yolakları üZerine Etkileriunclassified
“…[86][87][88] Diğer yandan retinoik asit sinyal yolaklarının gelişmekte olan ve erişkin beynindeki plastisiteyi etkiliyor olması, vitamin E'nin hücre sinyalizasyonu ve proliferasyonu üzerine olan etkileri ve vitamin C'nin gen ekspresyonu üzerine düzenleyici etkilerinin olabileceğine ilişkin veriler bu vitaminlerin normalden yüksek düzeylerinin ileride henüz öngöre-mediğimiz sonuçları olabileceğini akla getirmektedir. [25,41,63] Diğer yandan bu vitaminlerin eksikliklerine karşı da uyanık olmak gerekmektedir. Özellikle bazı psikiyatrik hastalıklarda hastaların sınırlı yeme tercihleri veya beslenme yetersizlikleri sebebi ile antioksidan vitaminler dahil birçok vitamin ve mineralin düşük düzeyleri söz konusu olabilir.…”
Section: Sonuçunclassified